Um curso de matemática básica através da resolução de problemas para alunos ingressantes da Universidade Federal do Pampa - campus Alegrete - Noguti, Fabiane Cristina Höpner [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present work investigates the use of Methodology of Mathematics Teaching-Learning- Evaluation through Problem Solving in the transition from Basic Education to College, applied in a Basic Mathematics Course. That investigation was conducted at Universidade Federal do Pampa – Alegrete Campus, with a group of 40 first-year students in Civil, Electrical, Mechanical and Telecommunications Engineering schools, and necessary Basic Mathematics contents were developed to follow the college disciplines. The research was grounded on Romberg’s Methodological Model in which, from the researcher’s phenomenon of interest, it was possible to identify three relevant topics: Problem Solving and College Education, Basic Education Mathematics necessary for College Education and Basic Mathematics Courses. The study of these topics and the support of other researchers’ ideas led to the research question: What are the contributions of a Basic Mathematics Course based on the Methodology of Mathematics Teaching-Learning-Evaluation through Problem Solving to help first-year college students in Mathematics disciplines, particularly Calculus I? From this research question, strategies and procedures were elaborated in order to answer it. Once the procedures were developed in classroom, the first-year students, by using the Methodology of Mathematics Teaching-Learning-Evaluation through Problem Solving, became co-builders of their own knowledge during the resolution of the proposed problems, which helped them review/build mathematical concepts and operation techniques in Basic Mathematics that are important for Calculus I. The data were collected through participant observation and the teacher-researcher’s records: diagnostic evaluation and questionnaires to students, field notes, students’ worksheets and videos of the meetings. For the analysis of the collected material, in order to answer the research question, we adopted a qualitative approach for...

Este trabalho investiga o uso da Metodologia de Ensino-Aprendizagem-Avaliação de Matemática através da Resolução de Problemas na transição da Educação Básica para o Ensino Superior, na forma de um Curso de Matemática Básica. Essa investigação foi realizada na Universidade Federal do Pampa – Campus Alegrete, com uma turma de 40 alunos ingressantes nos cursos de Engenharia Civil, Elétrica, Mecânica e de Telecomunicações, em que foram trabalhados conteúdos de Matemática Básica, necessários para o acompanhamento das disciplinas da graduação. Para o desenvolvimento da pesquisa foi utilizado o Modelo Metodológico de Romberg em que, a partir do fenômeno de interesse da pesquisadora, foi possível identificar três temas relevantes: a Resolução de Problemas e o Ensino Superior, a Matemática da Educação Básica necessária para o Ensino Superior e os Cursos de Matemática Básica. O estudo desses temas, apoiado nas ideias de outros pesquisadores levou à pergunta da pesquisa: Quais as contribuições de um Curso de Matemática Básica, utilizando-se da Metodologia de Ensino-Aprendizagem-Avaliação de Matemática através da Resolução de Problemas, para auxiliar os alunos ingressantes, nas disciplinas de Matemática, em particular do Cálculo I, no Ensino Superior? A partir da pergunta da pesquisa, forma elaboradas estratégias e procedimentos a fim de respondê-la. Colocados os procedimentos em ação em sala de aula, os alunos, utilizando a Metodologia de Ensino- Aprendizagem-Avaliação de Matemática através da Resolução de Problemas, atuaram como coconstrutores de seu conhecimento durante a resolução dos problemas propostos. Isso lhes possibilitou rever/construir conceitos matemáticos e técnicas operatórias de matemática básica importantes para o Cálculo I. Para a coleta dos dados, foram utilizadas a observação participante e os registros da professora-pesquisadora: avaliação diagnóstica e...
Keywords: Universidade Federal do Pampa; Mathematics - Study and teaching; Matemática - Estudo e ensino; Matemática - Estudo e ensino - Rio Grande do Sul; Matemática - Problemas, exercícios, etc; Universidades e faculdades - Curriculos; Estudantes universitarios; Ensino superior